IEES Intersubjectivity in a simultaneous scene Movement, Cyberspace and networked group creation - Tasso, Liliana (Revista Eletrônica MAPA D2 - Mapa e Programa de Artes em Dança (e Performance) Digital, 2014)
IEES is a piece of research, a networked multi-spatial performance, a human experience mediatized by technology, a door opening to a field barely explored yet. A group of artists from Buenos Aires and Barcelona bonds together and sets off a research and staging process exclusively through virtual connection. Different emotional intensities and/or emotional tensions inherent to human bonding eventually turned into thematic and climatic quality within the creation process itself. Every event in this mediatized relationship gained awareness and became the warp and weft of the real/virtual body of the group. The use of technological devices unfolded problems such as the considerable modification of the space-time concept, the presence/absence of the body revealing its identity through the image and tolerating the absence of real matter without a substantial loss of identity. Dialog, fusion and feedback between reality and virtuality. A barely-explored field opening to new dimensions for artistic and human development. A land offering itself to be conquered; a critical art that asks for new, fresh, creative energy to be withdrawn from the isolation of minority ghettos.